QCT of the proximal femur—which parameters should be measured to discriminate hip fracture?. Issue 3 (March 2016) - Museyko, O.; Bousson, V.; Adams, J.; Laredo, J.; Engelke, K.
Abstract Summary For quantitative computed tomography (QCT), most relevant variables to discriminate hip fractures were determined. A multivariate analysis showed that trabecular bone mineral density (BMD) of the trochanter with "cortical" thickness of the neck provided better fracture discrimination than total hip integral BMD. A slice-by-slice analysis of the neck or the inclusion of strength-based parameters did not improve fracture discrimination. Introduction For QCT of the proximal femur, a large variety of analysis parameters describing bone mineral density, geometry, or strength has been considered. However, in each given study, generally just a small subset was used. The aim of this study was to start with a comprehensive set and then select a best subset of QCT parameters for discrimination of subjects with and without acute osteoporotic hip fractures. Methods The analysis was performed using the population of the European Femur Fracture (EFFECT) study (Bousson et al. J Bone Min Res: Off J Am Soc Bone Min Res 26:881-893, 2011). Fifty-six female control subjects (age 73.2 ± 9.3 years) were compared with 46 female patients (age 80.9 ± 11.1 years) with acute hip fractures. The QCT analysis software MIAF-Femur was used to virtually dissect the proximal femur and analyze more than 1000 parameters, predominantly in the femoral neck. A multivariate best-subset analysis was used to extract the parameters best discriminating hip fractures. All results were adjusted for age, height, and weight differences between the two groups. Results For the discrimination of all proximal hip fractures as well as for cervical fractures alone, the measurement of neck parameters suffices (area under the curve (AUC) = 0.84). Parameters characterizing bone strength are discriminators of hip fractures; however, in multivariate models, only "cortical" cross-sectional area in the neck center remained as a significant contributor. The combination of one BMD parameter, trabecular BMD of the trochanter, and one geometry parameter, "cortical" thickness of the neck discriminated hip fracture with an AUC value of 0.83 which was significantly better than 0.77 for total femur BMD alone. A comprehensive slice-based analysis of the neck along its axis did not significantly improve hip fracture discrimination. Conclusions If QCT of the hip is performed, the analysis should include neck and trochanter. In particular, for fractures of any type, a comprehensive slice-based analysis of the neck along its axis did not significantly improve hip fracture discrimination nor did the inclusion of strength-related parameters other than "cortical" area or thickness. One BMD and one geometry parameter, in this study, the combination of trabecular BMD of the trochanter and of "cortical" thickness of the neck resulted in significant hip fracture discrimination.